2017
DOI: 10.33736/ijbs.512.2016
|View full text |Cite
|
Sign up to set email alerts
|

Relative Price Effects of Monetary Policy Shock in Malaysia: A Svar Study

Abstract: Studies on Malaysia monetary policy mostly examine the effect of monetary policy change on output and inflation in aggregate terms. While sectoral output effects of monetary policy have also been investigated, there is however a lack in the study on the effect of policy change on disaggregated inflation. This paper attempts to examine the later issue by employing structural vector autoregressive (SVAR) model. By estimating the model separately for each sub-group of Malaysian consumer price index, we find that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 32 publications
0
9
0
2
Order By: Relevance
“…For domestic block, several restrictions are drawn from existing studies that are related to the Malaysian economy and policy analysis (Karim & Karim, 2016;Raghavan, 2015;Raghavan, Silvapulle, & Athanasopoulos, 2012;Razmi et al, 2015Razmi et al, , 2016Shariq et al, 2016;Zaidi et al, 2013Zaidi et al, , 2016Zaidi & Fisher, 2010). As Malaysia is an oil exporting and emerging economy, shocks in global oil factors have impacts on the real sectors and stock market.…”
Section: Model Identificationmentioning
confidence: 99%
“…For domestic block, several restrictions are drawn from existing studies that are related to the Malaysian economy and policy analysis (Karim & Karim, 2016;Raghavan, 2015;Raghavan, Silvapulle, & Athanasopoulos, 2012;Razmi et al, 2015Razmi et al, , 2016Shariq et al, 2016;Zaidi et al, 2013Zaidi et al, , 2016Zaidi & Fisher, 2010). As Malaysia is an oil exporting and emerging economy, shocks in global oil factors have impacts on the real sectors and stock market.…”
Section: Model Identificationmentioning
confidence: 99%
“…Their results showed that, given the exposure of domestic monetary policy to foreign shocks, both money supply and interest rate are significant in stabilizing output and inflation in Malaysia. Subsequently, Zaidi and Karim (2014) and Zaidi et al (2016) extended the study on monetary policy shock in Malaysia into different direction. Zaidi and Karim (2014) further assessed the impact of several foreign shocks from Singapore, Japan, and the US on Malaysian economy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…By using a sign-restricted SVAR model, their results show that the foreign shock from Singapore appears to be the most dominant relatively to the shocks from the US and Japan. On the other hand, Zaidi et al (2016) examined the effect of monetary policy shock on disaggregated inflation. They found that a modest monetary policy shock would trigger different degree of responses in disaggregated inflation, in which the varying levels of price stickiness are observed in different sectors.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Jepun dalam mempengaruhi ekonomi di sesebuah negara adalah Zaidi et al (2016) yang mengkaji kesan kejutan dasar kewangan terhadap harga relatif di Malaysia.…”
Section: Antara Kajian Lain Yang Menggunakan Negara Amerika Danunclassified